The Effect of Dental Health Education through Leaflet Media on Student's Knowledge - Pinasti, Restika Anindya; Ghita Hadi Hollanda; Bambang Sucahyo (International Journal of Medical Science and Clinical Research Studies, 2024)
Introduction: The children aged 6-14 years are an age group that is critical for the occurrence of dental caries and has special characteristics, namely the period of replacement of deciduous teeth with permanent teeth. This group has a fairly high prevalence rate of dental caries, reaching 60-80%. In general development, dental caries looks very active at ages 4-8 years and ages 11-19 years. Based on the initial inspection at Hang Tuah 6 Elementary School Surabaya, there were 43 students with DMF-T index amount 4.5 in the high category. And the remaining data was obtained from 37 students, only 2 students were caries free. And it can be seen that the DMF-T index of 8.1 is a problem in this research, namely the high percentage of dental caries in students in 5th and 6th grade at Hang Tuah 6 Elementary School Surabaya in 2023. Purpose: This study purposes to analyze the relationship between knowledge on dental health education using leaflet media. Materials and Methods: The sampling technique used in this research is purposive sampling. The criteria for this research sample were students in 5th and 6th grade at Hang Tuah 6 Elementary School Surabaya. Data analysis using a simple linear regression statistical test with the aim of comparing the average results of the pre-test with the post-test in the intervention group, the decision to test the research hypothesis is based on the significant level < 0,05. Results: The characteristic of the respondents who were research subjects included age, gender, and number of students in each class. there is a variable influence of providing education through leaflet media on student's knowledge of dental and oral health Hang Tuah 6 Elementary School Surabaya. The table also explains the magnitude of the correlation/relationship value (R), which is 0.208. From this output, a coefficient of determination (R square) of 0.043 is obtained, which means that the independent variable to the dependent variable is 4,3%. Conclusions: The effect of dental health education using leaflet media on dental and oral health knowledge among students at Hang Tuah 6 Elementary School, Surabaya in 2023, this is based on a ρ value of 0.000<0.05, where H0 rejected and Ha accepted.